2018
DOI: 10.3758/s13421-017-0784-2
|View full text |Cite
|
Sign up to set email alerts
|

Attentional influences on memory formation: A tale of a not-so-simple story

Abstract: Is there a learning mechanism triggered by mere expectation violation? Is there some form of memory enhancement inherent to an event mismatching our predictions? Across seven experiments, we explore this issue by means of a validity paradigm. Although our manipulation clearly succeeded in generating an expectation and breaking it, the memory consequences of that expectation mismatch are not so obvious. We report here evidence of a null effect of expectation on memory formation. Our results (1) show that enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
2
18
2
Order By: Relevance
“…Lastly, and perhaps more interestingly, manipulations of congruency at the item level, which undoubtedly imply learning about specific items, still did not affect our participants' ability to recognize old items in any differential way. The absence of statistically significant differences when using null hypothesis significance testing, together with the use of Bayesian statistics to assess the likelihood of a null result in the presence of a true effect, greatly supports the claim that conflict at encoding does not directly lead to a better encoding of the target information (see Muhmenthaler & Meier, 2019;Ortiz-Tudela et al, 2016;Ortiz-Tudela et al, 2018;Ptok, Thomson, Humphreys, & Watter, 2019, for similar findings). Several accounts of cognitive control depict LWPCE and CSE as a reinstatement of a previous response set linked with specific stimulus features.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Lastly, and perhaps more interestingly, manipulations of congruency at the item level, which undoubtedly imply learning about specific items, still did not affect our participants' ability to recognize old items in any differential way. The absence of statistically significant differences when using null hypothesis significance testing, together with the use of Bayesian statistics to assess the likelihood of a null result in the presence of a true effect, greatly supports the claim that conflict at encoding does not directly lead to a better encoding of the target information (see Muhmenthaler & Meier, 2019;Ortiz-Tudela et al, 2016;Ortiz-Tudela et al, 2018;Ptok, Thomson, Humphreys, & Watter, 2019, for similar findings). Several accounts of cognitive control depict LWPCE and CSE as a reinstatement of a previous response set linked with specific stimulus features.…”
mentioning
confidence: 62%
“…The hypothesis of conflict-enhanced memory has been recently examined through several studies using different paradigms (Krebs, Boehler, De Belder, & Egner, 2015;Ortiz-Tudela, Milliken, Botta, LaPointe, & Lupiañez, 2016;Ortiz-Tudela, Milliken, Jiménez, & Lupiáñez, 2018;Rosner, D'Angelo, MacLellan, & Milliken, 2015a). For instance, Krebs et al (2015) used a face-word Stroop task, in which participants were asked to respond to the gender of a given set of faces that were overlaid with a distracting word (i.e., "MAN" or "WOMAN").…”
Section: Conflict Enhanced Memorymentioning
confidence: 99%
“…For example, Ortiz-Tudela and colleagues [ 47 ] reported that context-incongruent objects were detected more rapidly than context congruent objects, but they resulted in more discrimination errors in a recognition task. Ortiz-Tudela et al [ 48 ] also reported that incongruent objects were better detected but worse identified. Interestingly, while the previous studies that documented effects related to out-of-context targets typically used a much longer stimulus exposure duration, in the current experiments, we used a short presentation of the visual scenes (i.e., 500 ms).…”
Section: Discussionmentioning
confidence: 99%
“…Contextually mismatching objects are also more likely to be retrieved successfully after a short delay period [ 42 , 45 , 46 ]. It is, though, worth noting that context-incongruent facilitation appears to be extinguished at longer memory delays [ 47 , 48 ]. In the present study, we wanted to assess whether, and how, STM is affected by the interplay between crossmodal semantic congruence and the contextual congruence of the target object.…”
Section: Introductionmentioning
confidence: 99%
“…However, we see this conflict as positive in that it demonstrates that prediction error is not a fragile manipulation and in fact can be quite blunt. As long as expectations are violated, new learning has the potential to update old learning (Krawczyk et al, 2017; but also see Ortiz-Tudela et al, 2018). However, it is unclear why an obvious violation of expectations worked here while only very subtle and specific violations have been effective in other studies (e.g., Forcato et al, 2009).…”
Section: Discussionmentioning
confidence: 99%